2007
DOI: 10.1111/j.1745-493x.2007.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Reverse Auctions Revisited: An Analysis of Context, Buyer–Supplier Relations and Information Behavior

Abstract: SUMMARY This study investigates context, information behavior and buyer–supplier relationships in e‐reverse auctions (e‐RAs). Following a grounded theory approach, a comprehensive online questionnaire was developed and sent to both users and nonusers of e‐RAs. Usable responses were received from 89 buyers and 54 suppliers that were analyzed taking into account both the size and consistency of effects obtained from the Mann–Whitney U‐test and Kendall's tau (τ) statistic. The results not only show that e‐RAs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 51 publications
1
16
0
3
Order By: Relevance
“…a lot of hours going down the motorways to the different companies, going through the tender documents again and explaining what things were and explaining various aspects of it." Lösch and Lambert (2006) show that in e-RAs, buyers and suppliers place much greater emphasis on the collection and exchange of information than in other sourcing/sales situations. Unlike other scenarios, e-RAs require participating suppliers being comparable on all attributes except the price that will be negotiated through the auction itself.…”
Section: Information Behaviour and Buyer-supplier Relationships In E-rasmentioning
confidence: 97%
See 1 more Smart Citation
“…a lot of hours going down the motorways to the different companies, going through the tender documents again and explaining what things were and explaining various aspects of it." Lösch and Lambert (2006) show that in e-RAs, buyers and suppliers place much greater emphasis on the collection and exchange of information than in other sourcing/sales situations. Unlike other scenarios, e-RAs require participating suppliers being comparable on all attributes except the price that will be negotiated through the auction itself.…”
Section: Information Behaviour and Buyer-supplier Relationships In E-rasmentioning
confidence: 97%
“…Again, the fact that some participating suppliers have lost business in the e-RA may negatively affect their view. However, Lösch and Lambert (2006) found that buyers' decision-making indeed is biased and favours known or existing suppliers over new ones. Whether or not this finding confirm the often made suspicion that buyers only use e-RAs as a negotiation ploy (see Beall et al, 2003) to pressurize current suppliers remains arguable and requires further investigation.…”
Section: Synthesis Of the Research Findingsmentioning
confidence: 99%
“…Web-based procurement systems can enable significant improvements through a more strategic approach to obtain typically low-value, high-variety goods and services [10]. A study was undertaken to explore buyer-supplier relationships and participants' behaviors in e-reverse auctions (e-RAs) and the results indicated that e-RAs had fewer negative effects than are currently assumed [34]. The differences between buying organizations that have adopted reverse e-auctions and those that have not used e-auctions were explored and the findings suggested that e-auction adopters had higher annual sales than non-adopters [21].…”
Section: E-procurementmentioning
confidence: 98%
“…At the most basic level of knowledge sharing (Kannan and Tan 2002;Kwon and Suh 2004;Wagner and Buk 2005;Terpend, Tyler, Krause and Handfield 2008), buyer-supplier collaborations must exchange information (Petersen, Ragatz and Monczka 2005). Information exchange defines a bilateral expectation that parties will proactively provide pieces of information useful to their partner (Heide and John 1992;Lö sch and Lambert 2007). It involves frequently and informally transferring information about changes that may affect the other party (Moore 1998).…”
Section: Collaborative Buyer-supplier Relationshipsmentioning
confidence: 99%